NO-REFLOW PHENOMENON – MECHANISM, PREVENTION AND TREATMENT STRATEGIES - Szydłowski, Radosław; Bodera, Magdalena; Kaźmierska, Anna; Porwolik, Hanna; Rozmus, Sonja; Bylica, Dominik (International Journal of Innovative Technologies in Social Science, 2026)
No-reflow phenomenon is a major clinical problem in the treatment of acute myocardial infarction, which happens despite effective recanalization of the epicardial coronary arteries. It is also marked by compromised microvascular blood circulation and it is linked to poor clinical outcome, such as bigger infarct size, left ventricular remodeling and higher mortality rates. The lack of no-reflow pathophysiology is multifactorial in nature and consists of distal microthromboembolization, reperfusion injury, endothelial dysfunction, microvascular spasm, and excessive inflammatory response. The no-reflow diagnosis continues to be difficult. Angiographic techniques such as Thrombolysis In Myocardial Infarction (TIMI) flow grade, which are used widely, are not very effective in evaluating microvascular perfusion. Higher resolution imaging including cardiac magnetic resonance imaging, myocardial contrast echocardiography, among others, offer a more accurate analysis; nevertheless, their application in clinical practice is limited due to their infrequent availability and high cost. No-reflow phenomenon is also a complicated combating mechanism. The existing approaches to therapy are mainly directed at alleviating the burden of thrombus, limiting the area of infarction, and alleviating reperfusion damages. However, the efficacy of these methods is dynamic and inadequately frequently, and no single therapy aimed at the coronary microvascular dysfunction development is determined. This means that more investigations about the mechanism behind no-reflow, the creation of more sensitive diagnostic techniques, and specific treatment of no-reflow have to be taken to enhance microvascular reperfusion and patient outcome.